Examining Online Health Sciences Graduate Programs in Canada - Colley, Paige; Schouten, Karen; Chabot, Nicole; Downs, Matt; Anstey, Lauren; Moulin, Marc S.; Martin, Ruth E. (International Review of Research in Open and Distributed Learning, 2019)
Approximately one in 10 employed Canadians worked in health care and social services in 2016. Health professionals perceive life-long learning as an important element of professional life and value flexibility in their continuing education activities. Online learning is ideally suited to meet this need for flexible health sciences continuing education. The present study sought to identify and characterize online graduate programs in health sciences offered by Canadian universities. All Canadian (non-technical) university websites were hand searched for online graduate programs in health and related fields. Each identified program was characterized by 10 features: province, university, flexibility (i.e., fully online or blended), subject area, curriculum (e.g., coursework, thesis or project, practicum), duration and timing options (i.e., full-time, part-time), admission requirements, class size and acceptance rates, and employment outcomes. The search identified 171 Canadian university online graduate programs in health and related fields. Across Canada, the greatest numbers of programs are offered in Ontario and British Columbia. Most programs are master’s and graduate certificate programs, with graduate diploma and PhD programs being less common. While the majority of programs require an undergraduate degree for admission, some programs base entry requirements on previous work experience. Most programs offer a blended learning experience, with fewer being fully online. The most common content areas include nursing, public health, occupational health, and occupational therapy. These findings highlight opportunities to advance fully online, health continuing education in novel subject areas.